2018
DOI: 10.1111/ipd.12437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crown fracture treatment on oral health‐related quality of life of children, adolescents, and their families: A prospective clinical study

Abstract: Background Enamel‐dentin fracture causes impact on the oral health‐related quality of life (OHRQoL) of children. Aim To evaluate the impact of treatment of crown fracture involving enamel and dentin (CFED) in the permanent dentition on the OHRQoL of children and adolescents (C/As) and their families. Design This prospective clinical study included C/As between 8 and 14 years who presented anterior CFED treated thought direct composite resin restoration. Their parents/caregivers (P/Cs) were also invited to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 33 publications
(113 reference statements)
2
30
0
Order By: Relevance
“…The studies dealing with CPQ 8-10 instruments are applied on validation studies 10,12,[16][17][18][19] or studies about: specific oral conditions (dental caries, fluorosis; malocclusion; temporomandibular; oral habits); disorder or disorders such as cleft lip/cleft palate; or in a group of childhood cancer survivors [20][21][22][23][24][25][26][27] ; and also in a population that has suffered dental trauma. 2,7,28,29 In the present study, TDI has a significant impact on child's OHRQoL, which was supported by previous studies. 2,7 Schuch et al 7 observed that children aged from 8 to 10 years old with TDI had significantly more negative impact on their OHRQoL than those without TDI.…”
Section: Dental Trauma and Quality Of Lifesupporting
confidence: 91%
“…The studies dealing with CPQ 8-10 instruments are applied on validation studies 10,12,[16][17][18][19] or studies about: specific oral conditions (dental caries, fluorosis; malocclusion; temporomandibular; oral habits); disorder or disorders such as cleft lip/cleft palate; or in a group of childhood cancer survivors [20][21][22][23][24][25][26][27] ; and also in a population that has suffered dental trauma. 2,7,28,29 In the present study, TDI has a significant impact on child's OHRQoL, which was supported by previous studies. 2,7 Schuch et al 7 observed that children aged from 8 to 10 years old with TDI had significantly more negative impact on their OHRQoL than those without TDI.…”
Section: Dental Trauma and Quality Of Lifesupporting
confidence: 91%
“…Previous studies have reported that TDI occurrence, especially in anterior teeth, has consequences that may impact the aesthetics, 32 quality of life, 33,34 psychosocial behaviours 32 and social reception 8 of children and/or adolescents, and the treatment of TDI is necessary to minimize some of these negative impacts 35 . Once a tooth has been traumatized, local sequelae may occur immediately or over the months or years thereafter, 6,36 leading to the requirement of years of follow‐up after a dental trauma treatment, resulting in further direct and indirect costs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the impact of enamel fractures on OHRQoL among adolescents. The main finding was that enamel TA B L E 1 Characteristics associated with CPQ [11][12][13][14] Previous studies with different populations report that TDI exerts a negative on OHRQoL, [3][4][5] but no studies investigated the impact of enamel fracture alone on this outcome in adolescents. A previous study involving Brazilian children aged eight to ten years found no negative impact from enamel fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies and systematic reviews generally suggest that a traumatic dental injury (TDI) exerts an impact on the OHRQoL of children and adolescents . However, TDI includes a variety of tooth injuries with potentially different degrees of impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation